Democracy in practice - Catt, Helena (Routledge, 2002)
Evaluates the success of public participation and the contextual and procedural factors that lead to it. This book demonstrates that public participation has not only improved environmental policy, but it has also played an important educational role and has helped resolve the conflict and mistrust that often plague environmental issues.